PENGARUH LAMA PENYEDUHAN TERHADAP KADAR TANIN PADA TEH CELUP - Hayati, Mala (Universitas Muhammadiyah Surabaya)
PENGARUH LAMA PENYEDUHAN TERHADAP KADAR TANIN PADA TEH CELUPÂ Mala Hayati, STP, MKesProdi D3 Analis Kesehatan UM SurabayaAbstract Tea is the most widely consumed beverages by all levels of society because in addition to economical, tea is also thought to provide health benefits. Teabag tea is one favored by todays society because of easy and practical. One of the compounds in tea play a role in the health of the body is as an antioxidant tannins. The size of the tannin content received by the body depends on the way of processing tea before drinking. The longer the brewing time for tea bags will make the content of tannins in higher beverage.So that the problem statements in research is whether there is a long brewing tea influence on levels of tannins? The purpose of this study was to investigate the influence of long brewing on levels of tannins in tea bags. This type of research is experimental. The sample in this study is a tea bag that is often consumed by people who sold in Superindo Mulyosari area. The samples used in this study were 30 tea bags the size of 2 grams divided into 6 treatments each - each consisting of 4 repetitions. Variable in this study is the independent variable while the dependent variable brewing long that tannin levelsFrom the results of tannin levels based brewing long known that the average - average levels of tannins with brewing time 2 minutes, 4 minutes, 6 minutes, 8 minutes, 10 minutes and 12 minutes respectively were 0.0184%, 0.0398%, 0.0546%, 0.0936%, 0.1568% and 0.1578%. ANOVA test results showed the influence of the old brewing on levels of tannin in tea bags with a significant value of less than 0.05 or 5%.Â Keyword : tea, tanin level, long brewing